Comparative X-ray photoelectron spectroscopy analysis of nitrogen atoms implanted in graphite and diamond - Auciello, Orlando; Veyan, Jean-François; Arellano-Jimenez, Maria J. (Frontiers in Carbon, 2023)
Introduction: Insertion of N atoms at a nanoscale subsurface depth in single-crystal diamond (SCD) may enable new generations of quantum electronics devices. In this sense, it is critical to understand the interaction between implanted N atoms and C atoms in the diamond lattice. Methods: The investigation of the interaction of N atoms with SCD at the atomic scale using X-ray photoelectron spectroscopy (XPS) analysis involves in situ bombardment of the SCD surface with relatively low-energy (5,000 eV) N2 ions. In situ XPS analyses of SCD and highly oriented pyrolytic graphite (HOPG) before and after N-atom implantation are compared with published XPS analyses of C-N materials (e.g., g-CN, N in poly/single-crystal diamond). Results: The analyses revealed three N 1s peaks at 398–399 eV (N1), 399–400.5 eV (N2), and 401–403 eV (N3), with the N1 and N2 peaks assigned to C-N bonds and an N3 peak inaccurately assigned, in prior publications, to N-bonded contaminants (e.g., O, NH). In situ cleaning of the SCD and HOPG surfaces prior to N-atom implantation was performed to eliminate all atmospheric contaminants. This cleaning process revealed that the N3 peak is associated with N-C-bonded atoms and not the C-O/NH linkage, as previously suggested. Ex situ high resolution transmission electron microscopy (HRTEM) studies of N-implanted SCD show a defect-structured subsurface region. Discussion: An important side effect of the relatively low-energy N implantation in SCD is the formation of a 5–8 nm electrically conductive surface layer, an effect that may open the pathways for future research in diamond-based micro- and nano-electronics.